GE_GERICHTE C/7587/2012 vom 18. Dezember 2012 - GE Cour de justice (2012)
ADMINISTRATION DES PREUVES; OBLIGATION D'ENTRETIEN; REVENU DE LA FORTUNE | CPC.276.1; CPC.314.2; CPC.316.3; CC.163; CC.176.1.1